2017
DOI: 10.1007/s00604-017-2321-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipid bilayer membrane technologies: A review on single-molecule studies of DNA sequencing by using membrane nanopores

Abstract: Nanopores based on α-hemolysin and MspA represent attractive sensing platforms due to easy production and operation with relatively low background noise. Such characteristics make them highly favorable for sequencing nucleic acids. Artificial lipid bilayer membranes, also referred to as black lipid membranes, in conjunction with membrane nanopores, can be applied to both the detection and highly efficient sequencing of DNA on a single-molecule level. However, the inherently weak physical properties of the memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 101 publications
1
10
0
Order By: Relevance
“…From the governing equations, we also showed that the separation velocity scales with the square of the initial bilayer radius and that the bilayer decay magnitude scales inversely with initial bilayer radius -the rationale for increasing relaxation times and bilayer decay magnitudes observed in the experiments. These results improve our understanding of bilayer separation mechanics under step strain and supplements the scientific efforts aimed at characterizing separation mechanics of bilayers under different separation modes [3,22,31,37].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…From the governing equations, we also showed that the separation velocity scales with the square of the initial bilayer radius and that the bilayer decay magnitude scales inversely with initial bilayer radius -the rationale for increasing relaxation times and bilayer decay magnitudes observed in the experiments. These results improve our understanding of bilayer separation mechanics under step strain and supplements the scientific efforts aimed at characterizing separation mechanics of bilayers under different separation modes [3,22,31,37].…”
Section: Discussionsupporting
confidence: 57%
“…The phospholipid bilayer is an important component of cell membrane that regulates material transport in a wide range of conditions [1][2][3]. It was first extracted and identified by Gorter and Grendel in 1925 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nanopore technology has the potential for detecting and characterizing biomolecules including DNA , RNA and proteins , viruses , and polysaccharides . As biomolecules pass through the nanopore, they cause ionic current blockages, which can be analyzed to characterize physical and chemical properties of the biomolecule .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the glass nanopore approach presents smaller bilayer capacitance and lower noise. Other reported methods for this purpose include using precast gels to protect the planar bilayer and polymerization of phospholipid bilayer membranes [ 66 ]. Bayley et al [ 67 ] used a planar phospholipid bilayer with an embedded single biological α-HL nanopore and inserted it between two agarose gel layers.…”
Section: Nanopore Sensorsmentioning
confidence: 99%